Insider trading among central bankers: A treatise on temptation and policy choice - Michael Schinke; Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2006)
Corruption among central banks induces distorted policies by, first, increasing the inflation bias and, second, potentially inducing a pro-cyclical adjustment of employment. In response to a negative supply shock a corrupt central banker is tempted to decrease money supply. In this case, he pretends an ultraconservative attitude while in reality he is driven by self interest. If societies with extreme tastes (relating only to inflation or employment) are not governed by central bankers with similar preferences, corruption might be tolerated as an instrument of bringing factual policies more in line with its public desire. This finding provides a warning signal against the choice of non-representative central bankers.
Keywords: E5; K42; 330; Time-inconsistency; inflation bias; seignorage; stochastic supply side shocks; conservatives; populists